Given the equation:
![\text{ x}^2\text{ + 3x - 4 = 0}](https://img.qammunity.org/2023/formulas/mathematics/college/crqbc1j8cihh2pc8adq640r6hsw3vhzeki.png)
To find x, since the equation is in the standard form of Quadratic Equation, we will be using the Quadratic formula:
![\text{ x =}\frac{-b\text{ }\pm\text{ }\sqrt[]{b^2-4ac}}{2a}](https://img.qammunity.org/2023/formulas/mathematics/college/3levc1qi2thuvli7txr2zo6xutu46ahxv7.png)
At,
![ax^2\text{ + bx + c = 0}](https://img.qammunity.org/2023/formulas/mathematics/college/5g12tkramqxsv41d83rhxbcqeorituzjv5.png)
Where,
a = coefficient at x² = 1
b = coefficient at x = 3
c = constant = -4
Let's plug in the values to find for x:
![\text{ x =}\frac{-b\text{ }\pm\text{ }\sqrt[]{b^2-4ac}}{2a}](https://img.qammunity.org/2023/formulas/mathematics/college/3levc1qi2thuvli7txr2zo6xutu46ahxv7.png)
![undefined]()